Litter relocation behavior in two species of ground‐dwelling squirrels. (6th November 2019) - Aliperti, Jaclyn R.; Van Vuren, Dirk H.; Rossi, Aviva J.; Armitage, Kenneth B.
Abstract: Maternal investment in mammals may take many forms, including spatial relocation of offspring. Litter relocation behavior, in which a female moves her litter to a new location, has been reported for several species of carnivores and rodents but has received little study. We describe litter relocations during long‐term studies of two species of ground‐dwelling squirrels, yellow‐bellied marmots (YBM, Marmota flaviventer ) and golden‐mantled ground squirrels (GMGS, Callospermophilus lateralis ), to determine the distance and frequency of litter relocations and to explore possible explanations for litter relocation behavior. We observed 19 litters relocated by YBM mothers and 32 by GMGS mothers. Although YBM are much larger than GMGS, relocation distances for YBM (median = 46 m and range = 15–324 m) were not greater than those for GMGS (median = 79 m and range = 16–252 m), possibly because YBM home ranges in our study area were exceptionally small. Frequency of litter relocation was greater for GMGS (21% of litters produced) than for YBM (10%), perhaps because GMGS experience fewer social constraints or greater predation risk. We identified several possible costs (energy expenditure and vulnerability to predators while transporting young) and benefits (reduced exposure to predation risk, increased habitat quality, and social benefits) of litter relocation. Future studies should continue to explore litter relocations to better understand the ecological causes and consequences of this behavior.